2009
DOI: 10.1021/jp907030e
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of cis-, trans-, and 1,1-Dichloroethylene in the Ultraviolet Range: Characterization of Cl(2PJ) Elimination

Abstract: By using photofragment velocity imaging detection coupled with a (2 + 1) resonance-enhanced multiphoton ionization technique, the elimination channel of spin-orbit chlorine atoms in photodissociation of cis-, trans-, and 1,1-dichloroethylene at two photolysis wavelengths of 214.5 and 235 nm is investigated. Translational energy and angular distributions of Cl((2)P(J)) fragmentation are acquired. The Cl((2)P(J)) fragments are produced by two competing channels. The fast dissociation component with higher transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our quantum chemical calculations reveal important C-Cl bond lengthening at the optimized geometry of this state which could be nearly repulsive (see table 3). Several photodissociation studies have been reported in the wavelength region of 155-250 nm (8.00-4.96 eV) [7] or 222-304 nm (5.58-4.08 eV) [24] or at 214.5 nm (5.78 eV) and at 235 nm (5.28 eV) [25]. The loss of HCl [7] and Cl( 2 P J ) [24,25] were investigated.…”
Section: The Valence Transitions (See Figures 1 3(a) and 4)mentioning
confidence: 99%
“…Our quantum chemical calculations reveal important C-Cl bond lengthening at the optimized geometry of this state which could be nearly repulsive (see table 3). Several photodissociation studies have been reported in the wavelength region of 155-250 nm (8.00-4.96 eV) [7] or 222-304 nm (5.58-4.08 eV) [24] or at 214.5 nm (5.78 eV) and at 235 nm (5.28 eV) [25]. The loss of HCl [7] and Cl( 2 P J ) [24,25] were investigated.…”
Section: The Valence Transitions (See Figures 1 3(a) and 4)mentioning
confidence: 99%
“…We thus assume that the earlier observed H and Cl formation and Cl 2 , HCl, and H 2 elimination, ,,, along with the formation and rearrangement of three-membered cyclic compounds, are ensued by further C−H and C−Cl bond homolyses, rearrangements, molecular (Cl 2 , HCl, and H 2 ) elimination, and carbene additions, allowing formation of high-molecular C/H/Cl unsaturates. The observed three- and four-carbon compounds serve as examples of intermediate products arising from addition of carbenes and/or addition/recombination of C-centered radicals, while the observed dichloromethane and trichloromethane illustrate the possibility of cleavage of bonds between carbon atoms in intermediary products.…”
Section: Resultsmentioning
confidence: 93%
“…These compounds are considered to belong among hazardous materials, and their carbonization to cokes as well as mechanistic studies on their thermal decomposition have attracted only limited attention. The dichloroethenes are well-known to be UV photolyzed via a number of pathways (cleavage of HCl, Cl, and H 2 ) and to allow formation of C/H/Cl fragments whose recombination in the gas phase may result in deposition of carbon nanoparticles with Cl−C bonds. Such products of UV laser-induced carbonization of chloroethenes have not been yet studied, and we report on ArF and KrF laser photolysis of gaseous cis -, trans -, and gem -dichloroethenes and elucidate the structure of the gas-phase deposited products.…”
Section: Introductionmentioning
confidence: 99%